Cho ` x ,y , z ` khác nhau và `1/x +1/y+1/z= 0` Tính ` A = (yz)/(x^2 + 2yz) + (xz)/(y^2 + 2xz ) + (xy)/(z^2 + 2xy)`

Cho ` x ,y , z ` khác nhau và `1/x +1/y+1/z= 0`
Tính
` A = (yz)/(x^2 + 2yz) + (xz)/(y^2 + 2xz ) + (xy)/(z^2 + 2xy)`

2 bình luận về “Cho ` x ,y , z ` khác nhau và `1/x +1/y+1/z= 0` Tính ` A = (yz)/(x^2 + 2yz) + (xz)/(y^2 + 2xz ) + (xy)/(z^2 + 2xy)`”

  1.  Ta có 1/x+1/y+1/z=0 
    =>1/x+1/y=-1/z 
    =>(1/x+1/y)^3= (-1/z)^3 
    =>1/x^3+1/y^3+3.1/x.1/y.(1/x+1/y) =-1/z^3 
    =>1/x^3+1/y^3+1/z^3= -3.1/x.1/y.(1/x+1/y) =3/(xyz) (vì 1/x+1/y=-1/z) 
    Mặt khác: 1/x+1/y+1/z=0 
    =>(xy+yz+zx)/(xyz)=0 
    =>xy+yz+zx=0 
    A=yz/x^2 +2yz + xz/y^2+ 2xz + xy/z^2+ 2 xy 
    =xyz/x^3+xyz/y^3+xyz/z^3 +2(xy+yz+zx) (vì x,y,z khác 0) 
    =xyz(1/x^3+1/y^3+1/z^3) (vì xy+yz+zx=0) 
    =xyz.3/(xyz) (vì 1/x^3+1/y^3+1/z^3=3/(xyz) ) 
    =3 
    Vậy A=3.
    nnnnnnn
    Lời giải và giải thích chi tiết:
     

    Trả lời
  2. ĐK: x,y,z ne0
    1/x+1/y+1/z=0
    <=> (xy+yz+zx)/xyz=0
    =>xy+yz+zx=0
    => yz=-xy-zx
    Do đó:
    (yz)/(x^2+2yz)
    =(yz)/(x^2+yz+yz)
    =(yz)/(x^2+yz-xy-zx)
    =(yz)/((x^2-xy)+(yz-zx))
    =(yz)/(x(x-y)-z(x-y))
    =(yz)/((x-y)(x-z))
    =(-yz(y-z))/((x-y)(y-z)(z-x))
    Tương tự:
    $\bullet$ (zx)/(y^2+2zx)=(-zx(z-x))/((x-y)(y-z)(z-x))
    $\bullet$(xy)/(z^2+2xy)=(-xy(x-y))/((x-y)(y-z)(z-x))
    => A=(-xy(x-y)-yz(y-z)-zx(z-x))/((x-y)(y-z)(z-x))
    Mà -xy(x-y)-yz(y-z)-zx(z-x)
    =-xy(x-y)-yz(y-z)+zx(x-z)
    =-xy(x-y)-yz(y-z)+zx(x-y+y-z)
    =-xy(x-y)-yz(y-z)+zx(x-y)+zx(y-z)
    =(x-y)(zx-xy)+(y-z)(zx-yz)
    =x(x-y)(z-y)+z(y-z)(x-y)
    =-x(x-y)(y-z)+z(y-z)(x-y)
    =(x-y)(y-z)(z-x)
    => A=((x-y)(y-z)(z-x))/((x-y)(y-z)(z-x))=1

    Trả lời

Viết một bình luận

Câu hỏi mới